STRENGTHENING LOCAL CLIMATE ACTION: THE RESAN COMMUNITY’S TREE PLANTING RITUAL ADVOCACY MODEL - Tsabitah, Noviana Aribah; Gunawan, Yusriyah Sandi Hartuti (Journal Pena Wimaya, 2025)
Drought is a natural disaster that occurs in karst areas. Gunungkidul, which has karst soil types, faces the direct impact of climate change. In addition, government programs such as massive borehole drilling with the initial aim of overcoming drought potentially damage the flow of springs and environmental habitats. On the other hand, the Resan Community of Gunungkidul is present and conducts a tree-planting movement with special rituals as a sign of community dissatisfaction. This study aims to analyze the advocacy model applied by the Resan Community in localizing climate action and evaluating environmental awareness education among the community. This research uses a qualitative method by collecting data through interviews, observation, and analysis of previous research. The results show that the Resan community advocacy model educates the public about climate action and mobilizes the collective actions of local communities. This action includes various ritual activities of local wisdom that distinguishes it from environmental conservation movements. This is also in line with the program of Indonesia’s 2022 Nationally Determined Contribution (NDC) to improve ecosystem conservation and restoration through community education with local wisdom. The advocacy model applied in the Resan Community has proven effective in localizing climate action by involving the community.Keywords: Advocacy, Climate Action, Drought, Resan Community